Ukraine : Technical Assistance Report-Enhancing the Medium-Term Budget Framework and Preparing Expenditure Baseline. (IMF Staff Country Reports; Country Report ;, 2019)
This Technical Assistance paper on Ukraine focuses on enhancing the medium-term budget framework and preparing expenditure baselines. While the inclusion of a contingency provision in the budget is prudent, it will be important that it is well communicated and strongly defended. There is a risk that the provision will be a general policy reserve, which can undermine budget discipline and disincentivize medium-term planning. The Budget Declaration submitted to the Cabinet is a significant step forward and contains many sound elements of a medium-term budget document. The Ministry of Finance should continue to expand its content in future years to better explain the basis of fiscal plans and improve transparency. Key enhancements include providing greater explanation on the main drivers of the medium-term macroeconomic and fiscal projections, reporting on compliance with fiscal rules, and further expanding the fiscal risk statement. Credible and robust expenditure baselines will take time to develop and the Ministry of Finance will need to play a central role.